2021
DOI: 10.1038/s41467-021-22717-9
|View full text |Cite
|
Sign up to set email alerts
|

Sox9 and Rbpj differentially regulate endothelial to mesenchymal transition and wound scarring in murine endovascular progenitors

Abstract: Endothelial to mesenchymal transition (EndMT) is a leading cause of fibrosis and disease, however its mechanism has yet to be elucidated. The endothelium possesses a profound regenerative capacity to adapt and reorganize that is attributed to a population of vessel-resident endovascular progenitors (EVP) governing an endothelial hierarchy. Here, using fate analysis, we show that two transcription factors SOX9 and RBPJ specifically affect the murine EVP numbers and regulate lineage specification. Conditional kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 54 publications
(47 reference statements)
2
40
0
Order By: Relevance
“…Additionally, live imaging of skin wound healing studies identified the migration of tissue resident endovascular progenitors (EVP) into the centre of wound granulation tissue and subsequent differentiation. EVPs have been identified to reside in vasculature and can give rise to mature endothelial cells, forming a vascular network independent of angiogenesis in ischemic situations of skin would healing [ 7 , 81 ]. Increased angiogenesis and neovascularisation has also been observed in skin wound healing using human EPC as a therapy, selectively blocking αVβ3 integrins, endothelial extracellular vesicles, antioxidant administration such as bee venom and also the activation of the PI3-kinase/Akt pathway [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Endothelial Cell Heterogeneity In Homeostasis and Repairmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, live imaging of skin wound healing studies identified the migration of tissue resident endovascular progenitors (EVP) into the centre of wound granulation tissue and subsequent differentiation. EVPs have been identified to reside in vasculature and can give rise to mature endothelial cells, forming a vascular network independent of angiogenesis in ischemic situations of skin would healing [ 7 , 81 ]. Increased angiogenesis and neovascularisation has also been observed in skin wound healing using human EPC as a therapy, selectively blocking αVβ3 integrins, endothelial extracellular vesicles, antioxidant administration such as bee venom and also the activation of the PI3-kinase/Akt pathway [ 82 , 83 , 84 , 85 , 86 , 87 , 88 ].…”
Section: Endothelial Cell Heterogeneity In Homeostasis and Repairmentioning
confidence: 99%
“…Endothelial cells also undergo endothelial to mesenchymal transition (EndMT) in pathological contexts, for example in response to unique signals from their niche to transdifferentiate into fibroblasts contributing to cardiac fibrosis [ 92 , 93 ]. Indeed, the EndMT transition is central to wound healing as the pro-inflammatory and hypoxic wound site triggers EndMT in migrating endothelial cells from the local vascular bed [ 81 , 94 ]. Aberrant endothelial transdifferentiation, both delayed or advanced differentiation, can give rise to unstable vessels at the wound site resulting in excess scar tissue formation [ 81 ].…”
Section: Endothelial To Mesenchymal Transition (Endmt)mentioning
confidence: 99%
See 3 more Smart Citations